Mine roadway support tailings sand-based guniting composition and preparation method thereof
Patent Information
- Application Number
- CN202610740378.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-27
- Publication Date
- 2026-09-11
AI Technical Summary
[0008]鉴于此,本发明提出了一种矿山巷道支护用尾矿砂基喷浆组合物的制备方法,旨在解决现有用尾矿砂制备的矿山巷道支护喷浆材料全尾砂利用率低、早期强度不足、施工性能差以及耐久性不足的问题
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid waste resource utilization technology, and more specifically, to a tailings sand-based sprayed grout composition for mine roadway support and its preparation method. Background Technology
[0002] Mine roadway support is a crucial aspect of ensuring safe mine production, and shotcrete technology is widely used due to its ease of construction and adaptability. Currently, traditional shotcrete mainly uses cement and river sand as raw materials, which not only consumes large amounts of natural resources and energy but also results in high support costs. Meanwhile, my country's mines generate hundreds of millions of tons of tailings annually. Large-scale tailings accumulation not only occupies land resources but also poses significant environmental safety hazards such as dam failures and heavy metal pollution.
[0003] Using tailings sand to prepare shotcrete materials for mine roadway support can achieve large-scale disposal of tailings solid waste and reduce support costs, resulting in significant economic and environmental benefits. However, existing technologies have the following prominent problems: Low utilization rate of tailings: Most technologies can only utilize graded tailings (usually 0.075~0.6mm particle size). Fine-grained tailings (<0.075mm) are abandoned due to their low activity and high water demand. The overall utilization rate of tailings is less than 50%.
[0004] Insufficient early strength: The tailings itself has extremely low activity and is mainly composed of inert minerals such as quartz and feldspar, which results in a long initial setting time and low early strength of the shotcrete, making it unable to quickly meet the immediate bearing requirements of roadway support and increasing the risk of surrounding rock instability.
[0005] Poor construction performance: The poor particle size distribution and rough surface of the tailings result in poor workability and high viscosity of the slurry, making it easy to clog the pipe during downhole pumping; the rebound rate during injection is high, resulting in serious material waste.
[0006] Insufficient durability: The sprayed layer is prone to shrinkage and cracking, and has weak resistance to seepage and deformation; traditional alkaline quick-setting agents have poor compatibility with the cementitious system, which will cause the strength loss of the sprayed material to exceed 30% after 28 days, seriously affecting the long-term stability of the support structure.
[0007] Therefore, the present invention proposes a method for preparing a tailings sand-based shotcrete composition for mine roadway support, which has important practical significance. Summary of the Invention
[0008] In view of this, the present invention proposes a method for preparing a tailings sand-based shotcrete composition for mine roadway support, aiming to solve the problems of low utilization rate of tailings sand, insufficient early strength, poor construction performance and insufficient durability of existing mine roadway support shotcrete materials prepared from tailings sand.
[0009] This invention proposes a method for preparing a tailings sand-based shotcrete composition for mine roadway support, comprising the following preparation steps: The tailings produced in the mine are screened to obtain coarse tailings and fine tailings. The coarse tailings are mechanically activated and the fine tailings are compound activated. The activated coarse tailings and fine tailings are mixed to obtain tailings aggregate. A composite cementitious material is obtained by mixing and grinding sulfoaluminate cement clinker, granulated blast furnace slag powder and high-calcium fly ash. The whole tailings aggregate is then mixed with the composite cementitious material, composite activator, composite tensile fiber and expansion crack-resistant agent to obtain a dry mix. Polycarboxylate superplasticizer and mixing water are mixed to obtain a superplasticizer aqueous solution. The superplasticizer aqueous solution is added to the dry mixture and stirred to obtain a slurry. An alkali-free quick-setting agent is added to the slurry and mixed to obtain a tailings sand-based sprayed slurry composition for mine roadway support.
[0010] Furthermore, the screening specifically includes: The tailings produced in the mine are vibrated and screened to separate coarse tailings of 0.075~1.2mm and fine tailings of <0.075mm.
[0011] Furthermore, the mechanical activation treatment specifically includes: The coarse-grained tailings were ball-milled, with the ball-to-mass ratio controlled at (7~9):1, the rotation speed at 220~260 r / min, and the ball-milling time at 30~45 min.
[0012] Furthermore, the composite activation specifically includes: The fine-grained tailings were ball-milled, with the ball-to-mass ratio controlled at (10~12):1, the rotation speed at 300~350 r / min, and the ball-milling time at 90~120 min. During ball milling, 0.5%~1.0% of anhydrous ethanol by mass of the fine-grained tailings was added.
[0013] Furthermore, the mass ratio of the activated coarse-grained tailings to the activated fine-grained tailings is (6~7):(3~4).
[0014] Furthermore, the mass ratio of sulfoaluminate cement clinker, granulated blast furnace slag powder, and high-calcium fly ash is 2.5:5.5:2.
[0015] Furthermore, the composite activator is composed of an alkaline activator, a sulfate activator, and a nanocrystalline nucleus activator mixed in a mass ratio of 5:2.5:1.5; the alkaline activator is composed of quicklime and calcium hydroxide mixed in a mass ratio of 3.5:1; the sulfate activator is composed of anhydrous gypsum and alum stone mixed in a mass ratio of 2.5:1; and the nanocrystalline nucleus activator is composed of nano-silica and nano-calcium carbonate mixed in a mass ratio of 1.5:1.
[0016] Furthermore, the composite tensile fiber is composed of chopped basalt fiber and polypropylene coarse fiber mixed at a mass ratio of 1.5:1.
[0017] Furthermore, the alkali-free quick-setting agent comprises the following components in parts by weight: 45 parts aluminum sulfate, 6 parts calcium fluoroaluminate, 3 parts triethanolamine, 4 parts diethanolmonoisopropanolamine, 0.7 parts sodium gluconate, and 0.5 parts stabilizer.
[0018] The present invention also proposes a tailings sand-based shotcrete composition for mine roadway support.
[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention uses untreated tailings sand as aggregate. Through the synergistic effect of mechanical activation and chemical activation, the potential activity of fine-grained tailings is effectively activated, and the utilization rate of the whole tailings sand is greatly improved.
[0020] 2. This invention constructs a sulfoaluminate cement clinker-slag composite cementitious system, which, combined with quicklime-nano silica composite activator and alkali-free quick-setting agent, achieves rapid setting and high strength development of the sprayed grout.
[0021] 3. The rheological properties of the slurry of the present invention give the slurry good workability and pumpability, making it less prone to pipe blockage during downhole pumping; the low rebound rate during injection reduces material waste and improves construction efficiency.
[0022] 4. The alkali-free quick-setting agent of this invention has excellent compatibility with the sulfoaluminate cement clinker-slag composite cementitious system, avoiding the problem of significant strength loss in the later stage caused by traditional alkaline quick-setting agents; the addition of tensile fibers effectively inhibits the shrinkage cracking of the sprayed layer and improves the crack resistance, impermeability and deformation resistance of the sprayed layer. Detailed Implementation
[0023] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention. It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the present invention.
[0024] Furthermore, regarding the numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included within this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0025] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0026] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0027] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0028] This invention provides a method for preparing a tailings sand-based shotcrete composition for mine roadway support, characterized by comprising the following preparation steps: The tailings produced in the mine are screened to obtain coarse tailings and fine tailings. The coarse tailings are mechanically activated and the fine tailings are compound activated. The activated coarse tailings and fine tailings are mixed to obtain tailings aggregate. A composite cementitious material is obtained by mixing and grinding sulfoaluminate cement clinker, granulated blast furnace slag powder and high-calcium fly ash. The whole tailings aggregate is then mixed with the composite cementitious material, composite activator, composite tensile fiber and expansion crack-resistant agent to obtain a dry mix. Polycarboxylate superplasticizer and mixing water are mixed to obtain a superplasticizer aqueous solution. The superplasticizer aqueous solution is added to the dry mixture and stirred to obtain a slurry. An alkali-free quick-setting agent is added to the slurry and mixed to obtain a tailings sand-based sprayed slurry composition for mine roadway support.
[0029] Specifically, the polycarboxylate superplasticizer is an early-strength polycarboxylate-based high-efficiency superplasticizer; the expansion and crack-resistant agent is an ettringite-type expansion agent with a limited expansion rate of 0.02%~0.05% (in water for 7 days).
[0030] Specifically, the amount of polycarboxylate superplasticizer added is 0.3% to 0.6% of the mass of the composite cementitious material; the amount of mixing water added is 13% to 17% of the mass of the dry mixture.
[0031] Specifically, when adding the water-reducing agent aqueous solution to the dry mixture, the water-reducing agent aqueous solution is slowly added to the dry mixture while stirring. The addition time is controlled at 1 to 2 minutes, and stirring is continued for 3 to 4 minutes after the addition is completed.
[0032] In this invention, the sieving specifically involves: The tailings produced in the mine are vibrated and screened to separate coarse tailings of 0.075~1.2mm and fine tailings of <0.075mm.
[0033] Understandably, this invention addresses the characteristics of uneven particle size distribution and significant differences in the physicochemical properties of coarse and fine tailings by achieving graded treatment and utilization. On the one hand, it allows coarse tailings to serve as aggregate skeleton components, requiring only mild mechanical activation to meet strength and gradation requirements, thus avoiding energy waste caused by excessive grinding. On the other hand, it separates fine tailings that were originally difficult to utilize due to low activity and high water demand, creating conditions for subsequent high-energy mechanical-chemical composite activation and fully stimulating their potential cementitious activity. Simultaneously, by subsequently compounding coarse and fine activation components in proportion, the continuous gradation and bulk density of the aggregate can be precisely controlled, significantly reducing aggregate porosity and slurry water demand. This fundamentally solves the problems of poor workability, easy pump blockage, and slow strength development that exist when ungraded tailings are used directly.
[0034] In this invention, the mechanical activation treatment specifically includes: The coarse-grained tailings were ball-milled, with the ball-to-mass ratio controlled at (7~9):1, the rotation speed at 220~260 r / min, and the ball-milling time at 30~45 min.
[0035] Specifically, the specific surface area of the coarse-grained tailings after ball milling is 350~400 m². 2 / kg.
[0036] Understandably, by controlling the ball-to-mass ratio, rotation speed, and grinding time in a horizontal ball mill with a slight mechanical activation process, the 0.075~1.2mm coarse-grained tailings obtained from screening can be precisely modified. This avoids excessive grinding that would lead to energy waste and a surge in water demand. Through mechanical force, the coarse-grained tailings particles are roughened, have more angular edges, and develop microcracks, significantly improving their interfacial bonding strength with cementitious hydration products. At the same time, the surface lattice structure of inert minerals such as quartz and feldspar is slightly disrupted, increasing the surface energy of the particles and stimulating their weak potential activity, transforming them from completely inert aggregates into reactive aggregates with a certain degree of reactivity. In addition, the particle size distribution of the coarse-grained tailings can be further optimized, eliminating the adverse effects of individual excessively large particles on the pumpability and spray uniformity of the slurry.
[0037] In this invention, the composite activation specifically refers to: The fine-grained tailings were ball-milled, with the ball-to-mass ratio controlled at (10~12):1, the rotation speed at 300~350 r / min, and the ball-milling time at 90~120 min. During ball milling, 0.5%~1.0% of anhydrous ethanol by mass of the fine-grained tailings was added.
[0038] Specifically, the specific surface area of the fine-grained tailings after ball milling is 550~650 m². 2 / kg.
[0039] Understandably, on the one hand, the impact, grinding, and extrusion of high-energy mechanical forces not only further refine the fine-grained tailings particles to the nano- to submicron level, but also deeply disrupt the complete crystal lattice structure of inert minerals such as quartz and feldspar, generating a large number of lattice defects, broken bonds, and unsaturated valence bonds, significantly improving the surface energy and potential cementing activity of the particles, transforming them from inert fillers into highly active auxiliary cementing materials; on the other hand, anhydrous ethanol grinding aids can effectively adsorb onto the surface of newly formed particles, preventing particle agglomeration, improving grinding efficiency, reducing energy consumption, and avoiding excessive hydration of the particle surface.
[0040] In this invention, the mass ratio of the activated coarse tailings to the activated fine tailings is (6~7):(3~4).
[0041] Specifically, the activated coarse-grained tailings and the activated fine-grained tailings are fed into a twin-shaft mixer at a mass ratio of (6~7):(3~4) and mixed evenly.
[0042] Understandably, on the one hand, 60%–70% coarse-grained activated tailings can form a continuous and stable skeleton structure, providing the main mechanical support for the shotcrete matrix, while avoiding the problems of increased slurry viscosity, increased pumping resistance, and increased drying shrinkage caused by excessive fine particles. On the other hand, 30%–40% fine-grained activated tailings can fully fill the voids between coarse particles, maximizing the bulk density of the aggregate system and reducing the porosity to below 35%, significantly reducing the amount of cementitious materials and mixing water required to fill the voids. At the same time, its high activity can participate in the secondary hydration reaction, generating more hydration products to fill capillary pores and improve the density and strength of the matrix. In addition, this ratio can also enable the slurry to obtain optimal cohesiveness and water retention, avoiding both excessive coarse particles leading to segregation and increased spray rebound rate, and excessive fine particles leading to excessively viscous slurry that can clog pipes.
[0043] In this invention, the mass ratio of sulfoaluminate cement clinker, granulated blast furnace slag powder and high-calcium fly ash is 2.5:5.5:2.
[0044] Specifically, sulfoaluminate cement clinker, granulated blast furnace slag powder and high-calcium fly ash are fed into a vertical mill at a mass ratio of 2.5:5.5:2 and ground together for 5-10 minutes until uniformly mixed to obtain a composite cementitious material. Specifically, the sulfoaluminate cement clinker is grade 42.5R with a specific surface area of 380~420 m². 2 / kg, C4A3S content ≥55%; the granulated blast furnace slag powder is S105 grade, with a specific surface area of 450~500m². 2 / kg, vitreous content ≥90%, alkalinity coefficient M0 ≥1.0; the high-calcium fly ash is Class F, Grade II, CaO content ≥10%, and loss on ignition ≤5%.
[0045] It is understood that in the composite gel material of this invention, sulfoaluminate cement clinker serves as the core fast-hardening component. Its high C4A3S content allows for rapid hydration to generate a large number of needle-like ettringite crystals, providing the shotcrete material with an extremely fast setting speed and early strength of 3-24 hours, meeting the immediate load-bearing requirements of roadway support. Simultaneously, the micro-expansion effect generated by its hydration can initially compensate for the drying shrinkage of the slurry. Granulated blast furnace slag powder, as the main component contributing to later-stage strength, undergoes a continuous secondary hydration reaction under the dual activation of alkalinity and sulfate by a multi-stage composite activator, generating CSH gel and ettringite, significantly improving the shotcrete material's strength. The material achieves 28-day and long-term strength while replacing a large amount of cement to reduce costs and improve the density and impermeability of the matrix. High-calcium fly ash, as a regulating component, has a spherical particle morphology that can exert a ball-bearing effect to significantly improve the workability and pumpability of the slurry, reduce water demand, and its active CaO and glassy components can participate in the hydration reaction to further enhance the matrix strength and optimize the pore structure of the hydration products, thereby improving the frost resistance and durability of the sprayed layer. Through reasonable proportioning and synergistic effects, the three components achieve a balance between rapid setting and early strength of the sprayed material and stable development of later strength, while significantly reducing cement usage and CO2 emissions.
[0046] In this invention, the composite activator is composed of an alkaline activator, a sulfate activator, and a nanocrystalline nucleus activator mixed in a mass ratio of 5:2.5:1.5; the alkaline activator is composed of quicklime and calcium hydroxide mixed in a mass ratio of 3.5:1; the sulfate activator is composed of anhydrous gypsum and alum stone mixed in a mass ratio of 2.5:1; and the nanocrystalline nucleus activator is composed of nano-silica and nano-calcium carbonate mixed in a mass ratio of 1.5:1.
[0047] Specifically, the particle size of nano-silica is 10~15nm, and the specific surface area is 180~220m². 2 / g, the particle size of nano-calcium carbonate is 30~50nm.
[0048] It is understood that the alkaline activator in the composite activator of this invention, composed of quicklime and calcium hydroxide in a 3.5:1 ratio, can rapidly provide and maintain a highly alkaline environment in the system, breaking the silicon-oxygen and aluminum-oxygen bonds in the glassy structure of slag and fly ash, releasing active SiO2 and Al2O3 components, and providing a material basis for subsequent hydration reactions; the sulfate activator, composed of anhydrous gypsum and alunite in a 2.5:1 ratio, can continuously provide SO4. 2-Ions react with calcium aluminate and activated alumina in the system to generate a large number of needle-like ettringite crystals, which not only significantly accelerates the setting and hardening rate, but also provides major support for early strength development. The nanocrystalline nucleation activator, which is a 1.5:1 compound of fumed silica and nano-calcium carbonate, can provide a large number of heterogeneous nucleation sites in the early stage of hydration, greatly reduce the energy barrier of the hydration reaction, accelerate the generation rate of hydration products, and refine the crystal size and pore structure of the hydration products, thereby improving the density of the matrix and the interfacial bonding strength. The three components work synergistically in a 5:2.5:1.5 ratio to achieve a unity of rapid early activation and sustained later activation, effectively solving the technical problems of low activity and slow early strength development in the whole tailings-based cementitious system, while avoiding the defects of a single activator that easily leads to a decline in strength or an increase in shrinkage in the later stage.
[0049] In this invention, the composite tensile fiber is composed of chopped basalt fiber and polypropylene coarse fiber mixed in a mass ratio of 1.5:1.
[0050] Specifically, the chopped basalt fibers are 6-9 mm long, 13-15 μm in diameter, and have a tensile strength ≥800 MPa; the polypropylene coarse fibers are 12-19 mm long, 20-30 μm in diameter, and have a tensile strength ≥500 MPa.
[0051] It is understood that the short basalt fibers with a length of 6-9 mm and a diameter of 13-15 μm in the composite tensile fiber of this invention, with their high tensile strength, high elastic modulus and excellent corrosion resistance, can be uniformly dispersed inside the matrix, playing a bridging role in the initiation and propagation stages of microcracks, effectively inhibiting the generation and development of microcracks inside the matrix, and significantly improving the crack resistance and impermeability of the sprayed layer; while the coarse polypropylene fibers with a length of 12-19 mm and a diameter of 20-30 μm, with their good toughness and high elongation, can continue to transmit stress after macrocracks appear, preventing further crack penetration, greatly improving the toughness, impact resistance and deformation resistance of the sprayed layer, and avoiding brittle fracture of the sprayed layer; the synergistic effect of the two in the above ratio not only solves the problem that single short fibers cannot effectively control macrocracks, but also makes up for the defects of single long fibers in poor dispersion and insufficient inhibition of microcracks, and can significantly improve the integrity and long-term stability of the sprayed layer.
[0052] In this invention, the alkali-free quick-setting agent comprises the following components in parts by weight: 45 parts aluminum sulfate, 6 parts calcium fluoroaluminate, 3 parts triethanolamine, 4 parts diethanolmonoisopropanolamine, 0.7 parts sodium gluconate, and 0.5 parts stabilizer.
[0053] Specifically, the preparation method of the alkali-free quick-setting agent is as follows: take 45 parts of aluminum sulfate, 6 parts of calcium fluoroaluminate, 3 parts of triethanolamine, 4 parts of diethanol monoisopropanolamine, 0.7 parts of sodium gluconate, and 0.5 parts of stabilizer, mix them, add water, and adjust the solid content to 50%.
[0054] It is understood that the calcium fluoroaluminate component in the alkali-free quick-setting agent of the present invention can rapidly provide a large number of ettringite crystal nuclei in the early stage of hydration, inducing the rapid generation and aggregation of hydration products to form a network structure, significantly shortening the setting time; the aluminum sulfate component continuously provides Al 3+ Ions, and Ca in the system 2+ and SO4 2- The reaction generates a large number of needle-like ettringite crystals, providing key support for early strength development. The organic alcohol amine component improves the compatibility between the accelerator and cementitious particles through surface adsorption and complexation, promoting uniform hydration reaction and effectively inhibiting the loss of slump over time. The alkali-free characteristic of this accelerator with Na2O content ≤0.5% avoids the alkali-aggregate reaction and later strength reduction problems caused by traditional alkaline accelerators. In addition, it can also optimize the instantaneous rheological properties of the slurry at the nozzle, reduce material waste, and improve construction efficiency.
[0055] Specifically, the tailings aggregate, composite cementitious material, composite activator, composite tensile fiber, and expansion crack-resistant agent are fed into a twin-shaft forced mixer and stirred for 3-4 minutes until uniformly mixed to obtain a dry mixture. The composite cementitious material accounts for 30%-50% of the mass of the tailings aggregate, the composite activator accounts for 2.8%-7.3% of the mass of the tailings aggregate, the composite tensile fiber accounts for 0.12%-0.35% of the mass of the dry mixture, and the expansion crack-resistant agent accounts for 0.5%-1.5% of the mass of the dry mixture.
[0056] Specifically, the method of using the tailings sand-based shotcrete composition for mine roadway support of the present invention is as follows: the slurry is fed into a wet shotcrete machine and mixed with an alkali-free quick-setting agent. The working air pressure of the shotcrete is controlled at 0.25~0.35MPa, the shotcrete distance is 0.9~1.1m, the shotcrete angle is 85°~90° with the shotcrete surface, and a layered shotcrete process is adopted. The thickness of the first layer is controlled at 30~50mm. After the first layer has initially set, the second layer is shot. The interval between each layer is 5~10min. The total shotcrete thickness is determined according to the design requirements. After the shotcrete is completed, a curing agent is sprayed on the surface of the shotcrete for curing. The curing time is not less than 7 days.
[0057] Specifically, the amount of the alkali-free quick-setting agent added is 0.7% to 1.3% of the mass of the composite cementitious material.
[0058] Example 1 Raw material components: Composite activator: It is composed of an alkaline activator, a sulfate activator and a nanocrystalline nucleus activator in a mass ratio of 5:2.5:1.5. The alkaline activator is quicklime and calcium hydroxide in a mass ratio of 3.5:1. The sulfate activator is anhydrous gypsum and alunite in a mass ratio of 2.5:1. The nanocrystalline nucleus activator is nano-silica and nano-calcium carbonate in a mass ratio of 1.5:1.
[0059] Alkali-free quick-setting agent: 45 parts aluminum sulfate, 6 parts calcium fluoroaluminate, 3 parts triethanolamine, 4 parts diethanolmonoisopropanolamine, 0.7 parts sodium gluconate, 0.5 parts stabilizer, add water to adjust the solid content to 50%.
[0060] Polycarboxylate superplasticizer: Aolite P180 powder polycarboxylate superplasticizer is used.
[0061] Composite tensile fiber: It is made by mixing short-cut basalt fiber and polypropylene coarse fiber in a mass ratio of 1.5:1.
[0062] Expanding crack-resistant agent: It is an ettringite-type expanding agent.
[0063] Preparation method: S1. The tailings from the mine are fed into a vibrating screen for screening to separate coarse-grained tailings of 0.075~1.2mm and fine-grained tailings of <0.075mm. The coarse-grained tailings are then fed into a horizontal ball mill for mechanical activation at a ball-to-mass ratio of 8:1, a rotation speed of 240 r / min, and a grinding time of 40 min, yielding a specific surface area of 380 m². 2 / kg of activated coarse-grained tailings; the fine-grained tailings were fed into a planetary high-energy ball mill for ball milling at a ball-to-mass ratio of 11:1, a rotation speed of 330 r / min, and a grinding time of 105 min. Anhydrous ethanol was added as a grinding aid at 0.8% of the mass of the fine-grained tailings during the grinding process, resulting in a specific surface area of 600 m². 2 / kg of activated fine-grained tailings; the activated coarse-grained tailings and fine-grained tailings are mixed in a ratio of 6.5:3.5 to obtain total tailings aggregate; S2. Sulfoaluminate cement clinker, granulated blast furnace slag powder, and high-calcium fly ash are fed into a vertical mill at a mass ratio of 2.5:5.5:2 and ground together for 8 minutes to obtain a composite cementitious material. The whole tailings aggregate, composite cementitious material, composite activator, composite tensile fiber, and expansion crack-resistant agent are fed into a twin-shaft forced mixer and stirred for 3 minutes to obtain a dry mix. The mass of the composite cementitious material is 40% of the mass of the whole tailings aggregate, the mass of the composite activator is 4.5% of the mass of the whole tailings aggregate, the mass of the composite tensile fiber is 0.2% of the mass of the dry mix, and the mass of the expansion crack-resistant agent is 0.8% of the mass of the dry mix.
[0064] S3. Take 0.45% of the mass of the composite cementitious material and add it to 15% of the mass of the mixing water of the dry mixture to obtain a water-reducing agent aqueous solution. Slowly add the water-reducing agent aqueous solution to the dry mixture while stirring. Control the addition time between 1 and 2 minutes. After the addition is completed, continue stirring for 4 minutes to obtain the slurry. S4. Add 4.5% by weight of alkali-free quick-setting agent to the slurry to obtain a tailings sand-based sprayed slurry composition for mine roadway support.
[0065] Example 2 Raw material components: Composite activator: It is composed of an alkaline activator, a sulfate activator and a nanocrystalline nucleus activator in a mass ratio of 5:2.5:1.5. The alkaline activator is quicklime and calcium hydroxide in a mass ratio of 3.5:1. The sulfate activator is anhydrous gypsum and alunite in a mass ratio of 2.5:1. The nanocrystalline nucleus activator is nano-silica and nano-calcium carbonate in a mass ratio of 1.5:1.
[0066] Alkali-free quick-setting agent: 45 parts aluminum sulfate, 6 parts calcium fluoroaluminate, 3 parts triethanolamine, 4 parts diethanolmonoisopropanolamine, 0.7 parts sodium gluconate, 0.5 parts stabilizer, add water to adjust the solid content to 50%.
[0067] Polycarboxylate superplasticizer: Aolite P180 powder polycarboxylate superplasticizer is used.
[0068] Composite tensile fiber: It is made by mixing short-cut basalt fiber and polypropylene coarse fiber in a mass ratio of 1.5:1.
[0069] Expanding crack-resistant agent: It is an ettringite-type expanding agent.
[0070] Preparation method: S1. The tailings from the mine are fed into a vibrating screen for screening to separate coarse-grained tailings of 0.075~1.2mm and fine-grained tailings of <0.075mm. The coarse-grained tailings are then fed into a horizontal ball mill for mechanical activation at a ball-to-mass ratio of 9:1, a rotation speed of 260 r / min, and a grinding time of 45 min, yielding a specific surface area of 400 m². 2 / kg of activated coarse-grained tailings; the fine-grained tailings were fed into a planetary high-energy ball mill for ball milling at a ball-to-mass ratio of 12:1, a rotation speed of 350 r / min, and a grinding time of 120 min. Anhydrous ethanol was added as a grinding aid at 1% of the mass of the fine-grained tailings during the grinding process, resulting in a specific surface area of 650 m². 2 / kg of activated fine-grained tailings; the activated coarse-grained tailings and fine-grained tailings are mixed in a ratio of 7:3 to obtain total tailings aggregate; S2. Sulfoaluminate cement clinker, granulated blast furnace slag powder, and high-calcium fly ash are fed into a vertical mill at a mass ratio of 2.5:5.5:2 and ground together for 10 minutes to obtain a composite cementitious material. The whole tailings aggregate, composite cementitious material, composite activator, composite tensile fiber, and expansion crack-resistant agent are fed into a twin-shaft forced mixer and stirred for 4 minutes to obtain a dry mixture. The mass of the composite cementitious material is 50% of the mass of the whole tailings aggregate, the mass of the composite activator is 7.3% of the mass of the whole tailings aggregate, the mass of the composite tensile fiber is 0.35% of the mass of the dry mixture, and the mass of the expansion crack-resistant agent is 1.5% of the mass of the dry mixture.
[0071] S3. Take 0.6% of the mass of the composite cementitious material and add it to 17% of the mass of the mixing water of the dry mixture to obtain a water-reducing agent aqueous solution. Slowly add the water-reducing agent aqueous solution to the dry mixture while stirring. Control the addition time between 1 and 2 minutes. After the addition is completed, continue stirring for 4 minutes to obtain the slurry. S4. Add 5.5% (by weight of composite cementitious material) of alkali-free quick-setting agent to the slurry to obtain a tailings sand-based sprayed slurry composition for mine roadway support.
[0072] Example 3 Raw material components: Composite activator: It is composed of an alkaline activator, a sulfate activator and a nanocrystalline nucleus activator in a mass ratio of 5:2.5:1.5. The alkaline activator is quicklime and calcium hydroxide in a mass ratio of 3.5:1. The sulfate activator is anhydrous gypsum and alunite in a mass ratio of 2.5:1. The nanocrystalline nucleus activator is nano-silica and nano-calcium carbonate in a mass ratio of 1.5:1.
[0073] Alkali-free quick-setting agent: 45 parts aluminum sulfate, 6 parts calcium fluoroaluminate, 3 parts triethanolamine, 4 parts diethanolmonoisopropanolamine, 0.7 parts sodium gluconate, 0.5 parts stabilizer, add water to adjust the solid content to 50%.
[0074] Polycarboxylate superplasticizer: Aolite P180 powder polycarboxylate superplasticizer is used.
[0075] Composite tensile fiber: It is made by mixing short-cut basalt fiber and polypropylene coarse fiber in a mass ratio of 1.5:1.
[0076] Expanding crack-resistant agent: It is an ettringite-type expanding agent.
[0077] Preparation method: S1. The tailings from the mine are fed into a vibrating screen for screening to separate coarse-grained tailings of 0.075~1.2mm and fine-grained tailings of <0.075mm. The coarse-grained tailings are then fed into a horizontal ball mill for mechanical activation at a ball-to-mass ratio of 7:1, a rotation speed of 220 r / min, and a grinding time of 30 min, yielding a specific surface area of 350 m². 2 / kg of activated coarse-grained tailings; the fine-grained tailings were fed into a planetary high-energy ball mill for ball milling treatment, with a ball-to-mass ratio of 10:1, a rotation speed of 300 r / min, and a grinding time of 90 min. Simultaneously, anhydrous ethanol was added as a grinding aid at 0.5% of the mass of the fine-grained tailings during the grinding process, resulting in a specific surface area of 550 m². 2 / kg of activated fine-grained tailings; the activated coarse-grained tailings and fine-grained tailings are mixed in a ratio of 6:4 to obtain total tailings aggregate; S2. Sulfoaluminate cement clinker, granulated blast furnace slag powder, and high-calcium fly ash are fed into a vertical mill at a mass ratio of 2.5:5.5:2 and ground together for 5 minutes to obtain a composite cementitious material. The whole tailings aggregate, composite cementitious material, composite activator, composite tensile fiber, and expansion crack-resistant agent are fed into a twin-shaft forced mixer and stirred for 3 minutes to obtain a dry mix. The mass of the composite cementitious material is 30% of the mass of the whole tailings aggregate, the mass of the composite activator is 2.8% of the mass of the whole tailings aggregate, the mass of the composite tensile fiber is 0.12% of the mass of the dry mix, and the mass of the expansion crack-resistant agent is 0.5% of the mass of the dry mix.
[0078] S3. Take 0.3% of the mass of the composite cementitious material and add it to 13% of the mass of the mixing water of the dry mixture to obtain a water-reducing agent aqueous solution. Slowly add the water-reducing agent aqueous solution to the dry mixture while stirring. The addition time should be controlled between 1 and 2 minutes. After the addition is completed, continue stirring for 3 minutes to obtain the slurry. S4. Add 3.5% by weight of alkali-free quick-setting agent to the slurry to obtain a tailings sand-based shotcrete composition for mine roadway support.
[0079] Comparative Example 1 (Conventional Shotcrete) Mix river sand and silicate cement P.O42.5 in a ratio of 65:35, add 5% alkaline quick-setting agent by weight of cement and 16% water by weight of total mass.
[0080] Comparative Example 2 (Existing full tailings sand-based shotcrete material) Mix graded tailings (0.075~0.6mm), silicate cement P.O42.5, and quicklime in a ratio of 68:30:2, add 5% alkaline quick-setting agent by mass of cement, and 17% water by mass of total weight.
[0081] Test Example 1 (Slurry Workability Test) 1. Slump and spread test: The mixed slurry is placed into the slump test cylinder in three layers, and each layer is tamped 25 times with a tamping rod; The slump value is obtained by vertically lifting the slump cone and measuring the height difference between the height of the cone and the highest point of the slurry after slumping. After the slurry stops flowing, measure the maximum and minimum diameters of the slurry after it has expanded, and take the average value as the expansion value. Precautions: The entire test process should be completed within 5 minutes; the quick-setting agent should be added and stirred evenly within 30 seconds before the test.
[0082] 2. Setting time test: Prepare the slurry according to the formula, add the quick-setting agent and stir evenly, then immediately pour it into the test mold; Start timing from the addition of the quick-setting agent, and test with a Vicat apparatus every 30 seconds; When the test needle sinks into the slurry to a distance of 4±1mm from the bottom plate, the recorded time is the initial setting time. When the test needle sinks into the slurry by no more than 0.5 mm, the recorded time is the final setting time. Precautions: Avoid vibration of the mold during the test; after initial setting, the mold and slurry should be turned over together and the final setting time should be tested again.
[0083] Test Example 2 (Mechanical Property Test) 1. Compressive strength test: The specimen was prepared by the large-panel spraying method: the slurry was sprayed into a 450mm×350mm×120mm wooden mold, and the spraying direction was perpendicular to the sprayed surface; After spraying, cure under standard curing conditions until the specified age; The large plate was cut into 100mm×100mm×100mm cubic specimens using a cutting machine; Remove the specimen from the curing chamber and wipe off any surface moisture; Place the specimen on the pressure plate of the pressure testing machine, making the pressure-bearing surface of the specimen perpendicular to the spraying direction; The specimen was continuously and uniformly loaded at a loading rate of 0.5~0.8MPa / s until it failed. Record the failure load and calculate the compressive strength: f = F / A, where f is the cubic compressive strength (MPa), F is the failure load (N), and A is the bearing area of the specimen (mm²). 2 ).
[0084] 2.28d strength retention rate test: Two sets of specimens with the same ratio were prepared, one set with accelerator added and the other set without accelerator added; Both groups of specimens were cured under the same conditions for 28 days; The 28-day compressive strength of the two groups of specimens was tested separately. Calculation formula: R = (f1 / f0) × 100% In the formula: R is the 28d strength retention rate (%); f1 is the 28d compressive strength (MPa) of the specimen with added accelerator; f0 is the 28d compressive strength (MPa) of the specimen without added accelerator.
[0085] Test Example 3 (Construction Performance Test) 1. Rebound rate test: Lay a 1m² area under the spraying working surface. 2 plastic sheet Spray the slurry onto the wall above the plastic sheeting using the normal construction process, with the spraying time controlled within 1 minute. Collect the rebound material on the plastic sheet and weigh its mass m1. Calculate the total mass m0 of the sprayed material (by measuring the mass difference between the hoppers before and after spraying using the metering device of the spraying machine). Rebound rate calculation formula: η=(m1 / m0)×100% In the formula: η is the rebound rate (%); m1 is the mass of rebounded material (kg); m0 is the total mass of sprayed material (kg) Precautions: Tests should be conducted under the same spray parameters (wind pressure, distance, angle); each test should be repeated at least 3 times, and the average value should be taken.
[0086] Test Example 4 (Durability Test) 1. Drying shrinkage test: Prepare prism specimens with dimensions of 100mm × 100mm × 515mm; After molding, the specimen was cured in the mold for 24 hours, then demolded and the initial length L0 was measured. Place the specimen in a dry environment with a temperature of 20±2℃ and a relative humidity of 60±5%; The length Lt of the specimen was measured at 1d, 3d, 7d, 14d, 28d, 60d and 90d respectively; The formula for calculating the shrinkage rate is: ε = (L0 - Lt) / L In the formula: ε is the shrinkage rate at age t; L0 is the initial length of the specimen (mm); Lt is the length of the specimen at age t (mm); L is the gauge length of the specimen (mm, taken as 500mm).
[0087] 2. Impermeability test: Prepare a frustum specimen with an upper diameter of 175 mm, a lower diameter of 185 mm, and a height of 150 mm; After the specimens have been cured for 28 days, their sides are sealed and they are installed on the permeability tester. Start pressurizing from 0.1 MPa, and increase the water pressure by 0.1 MPa every 8 hours; When water seepage appears on the surface of 3 out of 6 specimens, stop the test and record the water pressure at this time; The impermeability grade is determined by multiplying the maximum water pressure value when no leakage occurs in 4 out of 6 specimens by 10. For example, when the maximum water pressure is 0.8 MPa, the impermeability grade is P8.
[0088] 3. Freeze-thaw resistance test: Prepare prism specimens of 100mm×100mm×400mm; After the specimens have been cured for 28 days, they are placed in a freeze-thaw test chamber. The freeze-thaw cycle temperature is controlled between -18±2℃ and 5±2℃, and the cycle time is 2~4 hours. The dynamic elastic modulus and mass of the specimen are tested once every 25 cycles. The test was stopped when the relative dynamic elastic modulus of the specimen dropped below 60% or the mass loss rate reached 5%. Freeze-thaw resistance rating determination: The maximum number of freeze-thaw cycles that the specimen can withstand is used as the freeze-thaw resistance rating. For example, if it can withstand 150 freeze-thaw cycles, the freeze-thaw resistance rating is F150.
[0089] Test Example 5 (Special Performance Test) 1. Pumping performance test: The mixed slurry is loaded into a pressure bleeding tester; Apply a pressure of 3.2 MPa and hold for 10 seconds; Open the drainage valve and collect the drainage volume V10 within 10 seconds and the drainage volume V140 within 140 seconds; Formula for calculating pressure-induced water leakage rate: B = (V10 / V140) × 100% In the formula: B is the pressure water exudation rate (%); V10 is the water exudation volume within 10s (mL); V140 is the water exudation volume within 140s (mL).
[0090] Evaluation criteria: When the pressure bleeding rate is ≤40%, the slurry has good pumping performance.
[0091] 2. Bond strength test: Spray a 50mm thick layer onto a rock or concrete substrate; After curing to the specified age, use a cutting machine to cut out square test blocks with a side length of 100mm from the sprayed layer, with the cutting depth reaching the surface of the base layer; Use a special adhesive to attach the steel drawing head to the surface of the test block; After the adhesive has cured, a pull-out test is performed using a pull-out tester, and the failure load is recorded. Bond strength calculation formula: τ=F / A In the formula: τ is the bond strength (MPa); F is the failure load (N); A is the area of the specimen (mm²). 2 ) The test results are shown in Table 1: Table 1 Performance Test Results As shown in Table 1, the slump of Example 1 reached 200 mm and the spread reached 500 mm, which were 25% and 31.6% higher than those of Comparative Example 1, and 37.9% and 47.1% higher than those of Comparative Example 2, respectively. The pressure bleeding rate was only 28.5%, far lower than the 42.3% and 46.7% of the comparative examples. This indicates that the present invention significantly improves the rheological properties and water retention of the slurry through graded activation of tailings to optimize aggregate gradation, the efficient dispersing effect of Aolite ART-P180 powder water-reducing agent, and the "ball effect" of high-calcium fly ash. This gives the slurry excellent pumpability, enabling continuous pumping over long distances of more than 500 m underground without pipe blockage, while ensuring uniformity and stability during injection.
[0092] The initial setting time of Example 1 was only 2.2 min, and the final setting time was 6.2 min, which were shortened by 76.8% and 65.6% compared with Comparative Example 1, and by 71.8% and 59.2% compared with Comparative Example 2, respectively. The 3-hour compressive strength reached 7.1 MPa, which was 4.7 times that of Comparative Example 1 and 2.5 times that of Comparative Example 2, respectively. The 24-hour compressive strength reached 19.2 MPa, which was 2.3 times that of Comparative Example 1 and 1.7 times that of Comparative Example 2, respectively. This is due to the ternary composite cementitious system of sulfoaluminate-slag-fly ash constructed in this invention, the gradient activation effect of multi-stage composite activators, and the synergistic effect of adaptable modified alkali-free quick-setting agents. It can form a stable hydration product network structure in a very short time, quickly provide support resistance, effectively prevent deformation and instability of the surrounding rock in the roadway, and significantly improve the safety of mine construction.
[0093] The 28-day compressive strength of Example 1 reached 35.4 MPa, which was 23.8% higher than that of Comparative Example 1 and 45.7% higher than that of Comparative Example 2. The 28-day strength retention rate was as high as 96.8%, which was much higher than that of the comparative examples (68.5% and 72.1%). This is because the alkali-free accelerator used in this invention avoids the problems of alkali-aggregate reaction and structural damage of hydration products caused by traditional alkaline accelerators. At the same time, the continuous secondary hydration reaction of slag powder and fine-grained activated tailings provides sufficient impetus for the later strength development, realizing the coordinated development of early and later strength and ensuring the long-term load-bearing capacity of the support structure.
[0094] The rebound rate of Example 1 was only 7.2%, which was 69.4% lower than that of Comparative Example 1 and 62.5% lower than that of Comparative Example 2. This is mainly attributed to the optimized rheological properties of the slurry, the good compatibility between the accelerator and the cementitious system, and the thickening effect of the hybrid fiber system, which enabled the slurry to adhere and harden rapidly after being sprayed onto the sprayed surface, greatly reducing the generation of rebound material, improving construction efficiency, and reducing material consumption and construction costs.
[0095] The 28-day drying shrinkage rate of Example 1 was only 0.027%, which was 60.3% lower than that of Comparative Example 1 and 50.9% lower than that of Comparative Example 2, respectively. The 28-day impermeability grade reached P10, and the frost resistance grade reached F150, both significantly better than the comparative examples. The 28-day bond strength reached 2.1 MPa, which was 1.75 times that of Comparative Example 1 and 2.33 times that of Comparative Example 2, respectively. This is because the present invention reduces the aggregate porosity through graded activation of tailings, refines the pore structure of hydration products through nanocrystalline nuclei activators, inhibits shrinkage cracking through a hybrid fiber system, and compensates for drying shrinkage with an expansion crack-resistant agent. These combined effects result in a sprayed layer with extremely high density, crack resistance, impermeability, and frost resistance, while significantly improving the bond strength with the surrounding rock. This effectively resists groundwater erosion and repeated deformation of the surrounding rock, significantly extending the service life of the support structure.
[0096] Example 1 achieves 100% resource utilization of all tailings, while Comparative Example 2 can only utilize 45% of the graded tailings, with a large amount of fine-grained tailings being discarded. Meanwhile, the relative cost of this invention is only 72% of traditional shotcrete, and 13% lower than existing all-tailings-based shotcrete materials. This not only solves the environmental safety hazards caused by tailings storage but also significantly reduces the cost of mine roadway support, aligning with the concepts of green mine construction and circular economy development.
[0097] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the specific implementation of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a tailings sand-based shotcrete composition for mine roadway support, characterized in that, The preparation steps include the following: The tailings produced in the mine are screened to obtain coarse tailings and fine tailings. The coarse tailings are mechanically activated and the fine tailings are compound activated. The activated coarse tailings and fine tailings are mixed to obtain tailings aggregate. A composite cementitious material is obtained by mixing and grinding sulfoaluminate cement clinker, granulated blast furnace slag powder and high-calcium fly ash. The whole tailings aggregate is then mixed with the composite cementitious material, composite activator, composite tensile fiber and expansion crack-resistant agent to obtain a dry mix. Polycarboxylate superplasticizer and mixing water are mixed to obtain a superplasticizer aqueous solution. The superplasticizer aqueous solution is added to the dry mixture and stirred to obtain a slurry. An alkali-free quick-setting agent is added to the slurry and mixed to obtain a tailings sand-based sprayed slurry composition for mine roadway support.
2. The method for preparing the tailings sand-based shotcrete composition for mine roadway support according to claim 1, characterized in that, The screening process specifically involves: The tailings produced in the mine are vibrated and screened to separate coarse tailings of 0.075~1.2mm and fine tailings of <0.075mm.
3. The method for preparing the tailings sand-based shotcrete composition for mine roadway support according to claim 1, characterized in that, The mechanical activation treatment specifically includes: The coarse-grained tailings were ball-milled, with the ball-to-mass ratio controlled at (7~9):1, the rotation speed at 220~260 r / min, and the ball-milling time at 30~45 min.
4. The method for preparing the tailings sand-based shotcrete composition for mine roadway support according to claim 1, characterized in that, The composite activation specifically refers to: The fine-grained tailings were ball-milled, with the ball-to-mass ratio controlled at (10~12):1, the rotation speed at 300~350 r / min, and the ball-milling time at 90~120 min. During ball milling, 0.5%~1.0% of anhydrous ethanol by mass of the fine-grained tailings was added.
5. The method for preparing the tailings sand-based shotcrete composition for mine roadway support according to claim 1, characterized in that, The mass ratio of the activated coarse tailings to the activated fine tailings is (6~7):(3~4).
6. The method for preparing the tailings sand-based shotcrete composition for mine roadway support according to claim 1, characterized in that, The mass ratio of sulfoaluminate cement clinker, granulated blast furnace slag powder, and high-calcium fly ash is 2.5:5.5:
2.
7. The method for preparing the tailings sand-based shotcrete composition for mine roadway support according to claim 1, characterized in that, The composite activator is composed of an alkaline activator, a sulfate activator, and a nanocrystalline nucleus activator in a mass ratio of 5:2.5:1.5; the alkaline activator is composed of quicklime and calcium hydroxide in a mass ratio of 3.5:1; the sulfate activator is composed of anhydrous gypsum and alunite in a mass ratio of 2.5:1; and the nanocrystalline nucleus activator is composed of nano-silica and nano-calcium carbonate in a mass ratio of 1.5:
1.
8. The method for preparing the tailings sand-based shotcrete composition for mine roadway support according to claim 1, characterized in that, The composite tensile fiber is composed of chopped basalt fiber and polypropylene coarse fiber mixed in a mass ratio of 1.5:
1.
9. The method for preparing the tailings sand-based shotcrete composition for mine roadway support according to claim 1, characterized in that, The alkali-free quick-setting agent comprises the following components in parts by weight: 45 parts aluminum sulfate, 6 parts calcium fluoroaluminate, 3 parts triethanolamine, 4 parts diethanolmonoisopropanolamine, 0.7 parts sodium gluconate, and 0.5 parts stabilizer.
10. The tailings sand-based shotcrete composition for mine roadway support prepared by the method described in claim 1.